Strategi Meningkatkan Penjualan Fasilitas QRIS Guna Mempermudah Melakukan Transaksi Pada Bank BJB Kantor Cabang Pembantu Surya Kencana - Muhammad Rappi; Uluan Silaen (Jurnal Aplikasi Bisnis Kesatuan, 2022)
The development of the internet is increasing day by day both in technology and in its use, with the many features of payment features or transactions using digital banking facilities in this growing era, customers can make transactions using digital banking services that have been provided by banks such as internet banking, m-bangking, sms. banking or now customers can make payments or transactions with one click using a QR code. The purpose of this discussion is to find out how the public knows how customer knowledge is with the development of digital banking as well as to make it easier for customers to make transactions using digital banking. The results of the discussion show that the strategy for offering QRIS facilities at PT. Bank Pembangunan Daerah Jawa Brat and Banten, Tbk KCP Surya Kencana if the customer is interested in using this facility the customer must apply for the facility by filling out a form as well as other complementary documents, and the use of this facility can be beneficial for PT. Regional Development Bank Jawa Brat and Banten, Tbk KCP Surya Kencana and also for customers who use this QRIS facility. Keywords: digital banking